A novel metaheuristic approach for control of SEPIC converter in a standalone PV system - Dheeban Sembulingam Sankaralingam; Muthu Selvan Balasubramanian Natarajan; Maheswari Muthusamy; Sarojini Bagavath Singh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Fossil fuels are being replaced by renewables. Most of the renewables are intermittent, to have reliable power the renewables have to be conditioned before injecting into the utility grid. The DC-DC converters are perfect power electronic devices for conditioning the renewables. The single ended primary inductor converter (SEPIC) performs the conditioning with a very high voltage transfer gain and minimum ripples. The maximum power extraction from the PV panels is required for providing good quality DC power. Intelligent controllers can make use of optimization techniques. The particle swarm optimization (PSO) technique can optimize the controller to extract the maximum power. The SEPIC converter duty variation is optimized and a comparative analysis with the Buck-Boost converter is done in a MATLAB/Simulink environment. The proposed SEPIC converter system performed well by improving the power tracking by 40% and the system has been analysed in a battery charging environment.